Phytochemical and Bioactivity Studies from Plectranthus ecklonii† - Márcia Santos Filipe; Eva María Domínguez-Martín; Ana María Díaz-Lanza; Salvatore Princiotto; Patricia Rijo (Medical Sciences Forum, 2022)
Plectranthus is a well-known genus belonging to the Lamiaceae family and is mainly distributed in tropical areas of the globe. Furthermore, Plectranthus species are particularly rich in phenolic compounds and abietane-type diterpenes, such as royleanones, widely used in traditional medicine against a vast range of diseases, including skin disorders and cancer. In order to study the phytochemical composition and the biological activity of P. ecklonii Benth., ultrasound-assisted extractions were carried out using methanol and acetone as solvents. It is known from the literature data that phenolic compounds are predominant in the methanol extracts, while the phytochemical analysis of the acetone extracts from our research group evidenced abietanes as the most frequently occurring secondary metabolites. Methanol extracts were screened to assay their potential bioactivity as antimicrobials, antioxidants, and on skin-related enzymes, as well as their general toxicity. The results showed only a moderate effect against bacteria, but a very promising antioxidant activity, and no relevant general toxicity. High tyrosinase inhibition was observed, together with an excellent inhibitory activity on collagenase, making the methanolic extract a promising raw material to be used for the development of dermo-cosmetic formulations, especially those with antiaging activity. Fractionation and further purification were carried out on the acetone extracts, highlighting a significant cytotoxic activity, mainly due to the presence of diterpenes, with an observed IC50 in the low-micromolar range. Considering the potential applications for internal and topical uses, further studies are currently ongoing on both the extracts to investigate other relevant biological activities and ascertain their safety.